Pharmakon - Cole, Teju 1975- (MACK, 2024)
Bringing together a sequence of subtle and disquieting photographs with a dozen compact short stories, Pharmakon is a surprising new work from the singular mind of Teju Cole. The photographs were taken across the globe and extend the oblique point of view he developed in Fernweh (2020). Interspersed among the images are texts that emerge like intimate signals from our age of crisis, mining further the exquisite linguistic control that characterizes Cole’s novels Open City (2011) and Tremor (2023). The result is a work of strange beauty that startles and consoles in equal measure
Includes bibliographical references and index
Keywords: Cole, Teju -- 1975-; Fotografie; Cole, Teju; Photography, Artistic; Short stories; Photographie artistique; Nouvelles; art photography; short stories; Bildband